Cortical adult neurogenesis and its biological implication. Issue 1 (11th July 2021) - Ohira, Koji
Abstract: It is well established that adult neurogenesis occurs in the subventricular zone and the subgranular zone, but a controversy remains about adult neurogenesis in other regions. The cerebral cortex is the most controversial site and has long been of interest to not only neuroscientists, but also scientists with broad backgrounds and medical doctors since the late 19th century. However, recent studies have been gradually clarifying that neurogenesis in the adult cerebral cortex occurs, especially under pathological conditions. These studies suggest that endogenous neural stem cells and/or progenitor cells might exist in or around the cerebral cortex, and be useful for regenerative cell therapy in cases of brain insults and diseases. In this review, recent literature regarding neurogenesis in the adult cerebral cortex is summarized, and the possibility of cell therapy for cortex‐related disorders is discussed. Abstract : Recently, adult neurogenesis has been found in the cerebral cortex of mammals, including rodents and primates. In this review, I summarize recent literature, and discuss the meaning of cortical adult neurogenesis in cell therapy for brain diseases.